Characterization of a Neutron Beam Following Reconfiguration of the Neutron Radiography Reactor (NRAD) Core and Addition of New Fuel Elements - Aaron E. Craft; Bruce A. Hilton; Glen C. Papaioannou (Nuclear Engineering and Technology, 2016)
The neutron radiography reactor (NRAD) is a 250 kW Mark-II Training, Research, Isotopes, General Atomics (TRIGA) reactor at Idaho National Laboratory, Idaho Falls, ID, USA. The East Radiography Station (ERS) is one of two neutron beams at the NRAD used for neutron radiography, which sits beneath a large hot cell and is primarily used for neutron radiography of highly radioactive objects. Additional fuel elements were added to the NRAD core in 2013 to increase the excess reactivity of the reactor, and may have changed some characteristics of the neutron beamline. This report discusses characterization of the neutron beamline following the addition of fuel to the NRAD. This work includes determination of the facility category according to the American Society for Testing and Materials (ASTM) standards, and also uses an array of gold foils to determine the neutron beam flux and evaluate the neutron beam profile. The NRAD ERS neutron beam is a Category I neutron radiography facility, the highest possible quality level according to the ASTM. Gold foil activation experiments show that the average neutron flux with length-to-diameter ratio (L/D) = 125 is 5.96 × 106 n/cm2/s with a 2σ standard error of 2.90 × 105 n/cm2/s. The neutron beam profile can be considered flat for qualitative neutron radiographic evaluation purposes. However, the neutron beam profile should be taken into account for quantitative evaluation.